2015
DOI: 10.1186/s12879-015-1243-y
|View full text |Cite
|
Sign up to set email alerts
|

Differences in clinical characteristics and prognosis of Penicilliosis among HIV-negative patients with or without underlying disease in Southern China: a retrospective study

Abstract: BackgroundThe incidence of Penicillium marneffei infection has recently increased. This fungus can cause fatal systemic mycosis in both immunocompetent and immunocompromised patients without HIV infection.MethodsWe retrospectively analysed Penicilliosis patients between January 1, 2003 and August 1, 2014 at the First Affiliated Hospital of Guangxi Medical University. HIV-negative patients with Penicilliosis were divided into two groups: patients with underlying disease (Group D) and patients without underlying… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
41
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(43 citation statements)
references
References 11 publications
1
41
0
Order By: Relevance
“…The mortality of the patients is 16.7%, which is similar to that in the previous studies. 19,23,[27][28][29][30] Besides low CD4 T-cell count, the well-known predictor of bad outcome, low hemoglobin level is also associated with increased mortality risk in this study. This is different from the previous studies.…”
Section: Discussionmentioning
confidence: 91%
“…The mortality of the patients is 16.7%, which is similar to that in the previous studies. 19,23,[27][28][29][30] Besides low CD4 T-cell count, the well-known predictor of bad outcome, low hemoglobin level is also associated with increased mortality risk in this study. This is different from the previous studies.…”
Section: Discussionmentioning
confidence: 91%
“…T. marneffei has gradually spread from HIV‐infected persons to the general population. It is also seen increasingly in immunocompetent hosts in China and death has been reported in immunocompetent children . T. marneffei in immunocompetent hosts can be manifested as disseminated infection, focal abscesses, osteolytic destruction, or purulent pneumonia.…”
Section: Discussionmentioning
confidence: 99%
“…[2][3][4][5]7 However, T. marneffei complicated by LCH has not been reported. LCH is a proliferation of Langerhans cells mixed with inflammatory cells, particularly eosinophils, characterized by the expression of CD1a and S100 protein, and the presence of Birbeck granules on ultrastructural examination.…”
Section: Discussionmentioning
confidence: 99%
“…Systemic intravenous amphotericin B and itraconazole are the main effective treatment options. [1][2][3][4][5] However, in case 1, after 10 months of regular and adequate antifungal treatments, but without treatment of LCH, the patient ultimately died. This outcome suggested that it is essential to treat not only the secondary infection, but also the underlying disease such as connective tissue diseases, etc.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation